The Effectiveness of the Combination of Cinnamon and Ginger with Exercise Training in the Treatment of Dysmenorrhea and Premenstrual Syndrome - B Ebrahimi Azmoudeh; M Habibian; B Askari (Iran University of Medical Sciences, 2019)
Background & Aims: Dysmenorrhea and premenstrual syndrome (PMS) are common disorders in women, which affect different aspects of life. The present study aimed to evaluate the effectiveness of the combination of cinnamon and ginger with walking and stretching exercises on dysmenorrhea and PMS. Materials & Methods: This quasi-experimental study was conducted with a pretest-posttest design and a control group on 100 women with PMS in Qaemshahr, Iran in 2019. The patients were selected via convenience sampling and divided into four groups of 25 by drawing lots. The groups included exercise, cinnamon-ginger, combination of exercise and cinnamon-ginger, and control. The exercise training program comprised of stretching exercises and walking three sessions per week for eight weeks. A cinnamon-ginger capsule (500 mg) was administered thrice daily with the onset of pain within the first 72 hours of menstruation for two months. The patients were assessed before and eight weeks after the intervention using the visual analogue scale (VAS) of menstrual pain intensity, PMS screening tool, and PMS daily status. Data analysis was performed using paired t-test, the Mann-Whitney U test, one-way analysis of variance (ANOVA), Kruskal-Wallis test, and Tukey's test. Results: After eight weeks, the intensity and duration of primary dysmenorrhea and scores of the physical and mental symptoms of PMS significantly decreased in the intervention groups compared to the control group (P<0.05). Furthermore, the effects of the combination therapy on the percentage of the changes in the intensity and duration of primary dysmenorrhea pain and scores of the physical and mental symptoms of PMS were more significant compared to the cinnamon-ginger and exercise groups. Conclusion: According to the results, the non-pharmacological interventions of walking and stretching exercises, the simultaneous consumption of cinnamon-ginger, and combination therapy could significantly decrease the intensity and duration of primary dysmenorrhea pain and improving the physical and psychological symptoms of PMS. Therefore, these approaches are recommended as safe and effective therapies for the treatment of these disorders.